Answer:
Circle Equation: ( x - 3.8 )^2 + ( y - 7.8 )^2 = 25/36
Explanation:
* Knowing a circle equation is in the format (x – h)^2 + (y – k)^2 = r^2, with the center being at the point (h, k) and the radius being "r" *
Let us substitute values into this equation; provided ( 3.8, 7.8 ) is the center:
( x - 3.8 )^2 + ( y - 7.8 )^2 = r^2,
Now substitute value of r, or rather the radius 5/6:
( x - 3.8 )^2 + ( y - 7.8 )^2 = ( 5/6 )^2 ⇒
Circle Equation: ( x - 3.8 )^2 + ( y - 7.8 )^2 = 25/36
* Sorry this wasn't answered earlier *